The influence of socio-demographic factors on social cultural impacts of tourism: Case study of Masooleh and Saree'n, Iran - Zamani, F.H.; Musa, G.; Abessi, M. (2008)
This study explores the social cultural impacts of tourism as perceived by local residents with case studies of Masooleh and Sar'een in Iran. Using convenient sampling, the questionnaire was distributed to door to door in the two towns. From 500 useable questionnaires analyzed, residents large experience positive socio-cultural impact of tourism. Socio-demographic profiles of gender, educational level and tourism-related job influence the perception of socio-cultural impacts of tourism in the areas. The paper also suggests some management implications of the research findings.